2016
DOI: 10.1590/2317-1545v38n2156374
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in fiber naturally colored cottonseeds during storage

Abstract: -The cotton seeds deterioration process with different chemical composition, in distinct environments is essential to the definition of adequate methods for storage. The deterioration involves cellular, metabolic and chemical changes and the behavior of the seeds' antioxidant defense system has an important role to control the speed and intensity of this process. The colored fiber of cottonseeds cv. BRS Verde and white fiber cv. BRS 187-8H were stored under controlled environment conditions (10 °C, 25 °C and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Moreover, accumulation of carbohydrates and proteins, such as oligosaccharides and heat-shock proteins affects the tolerance of desiccation ( Waters et al, 1996 ; Bailly et al, 2001 ). Changes in lipid content are associated with the reduction of physiological quality, and reduction in fat content indicates loss of quality during storage ( Oliveira et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, accumulation of carbohydrates and proteins, such as oligosaccharides and heat-shock proteins affects the tolerance of desiccation ( Waters et al, 1996 ; Bailly et al, 2001 ). Changes in lipid content are associated with the reduction of physiological quality, and reduction in fat content indicates loss of quality during storage ( Oliveira et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who evaluated the physiological quality of different seeds stored under different conditions (Belmiro et al, 2010;Oliveira et al, 2012;Silva et al, 2010;Zuchi et al, 2013) also observed this fact. This is directly related to respiratory activities (Oliveira et al, 2016), and lipid peroxidation may be the most frequent cause of seed deterioration and viability loss (Abreu et al, 2013). Also, the lower the water content, the greater the amount of energy needed for the seed to come into balance with the environment.…”
Section: Resultsmentioning
confidence: 99%
“…From the results obtained it can be inferred that the ozone gas, considered to have high power of oxidation (Karaca et al, 2010;Khadre et al, 2001), the main reason to be used in disinfectant processes (Cataldo, 2008;Karaca & Velioglu, 2009;Karaca et al, 2010), did not influence the physiological quality of soybean seeds, once that oxidative processes are considered one of the main physiological quality reducer in oilseeds, such as soybean, due to free radicals formation caused by oxidation on cellular tissues and reserve components such as lipids, which are more susceptible to these effects (Oliveira et al, 2016).…”
Section: Discussionmentioning
confidence: 97%